ANALISIS PERBEDAAN MAKNA DASAR KATA DALAM BAHASA INDONESIA DAN BAHASA MALAYSIA (Analysis of Word Basic Meaning Differences in Indonesian and Malaysian Language) - Emmy Erwina (SAWERIGADING, 2021)
AbstractThis study examines the difference between the meaning of Indonesian and Malaysian. The data gathered for analysis will be used to determine the level of understanding of the various meanings of Indonesian and Malaysian vocabulary that have the same form but different meanings as well as meaning differences between Indonesian and Malaysian vocabulary that have different forms but have the same meaning. The methodologyused in this study was design an analysis of the different meanings of Indonesian and Malaysian, wich were from a survey distributed to 141 respondents via Google Form. The purpose of this study was to a betterunderstanding of differences in word usage between Indonesian and Malaysian. According to the findings of this study, researcher will produce data on the level off understanding of the different meanings of Indonesianand Malaysian as well as differences in word usage in Indonesian and Malaysian. The level of understanding of respondents related to this study was 78 percent understanding of the correct classification of meanings intoIndonesian vocabulary and 69.6 percent for a good understanding of the correct classification of meanings into to Malaysian vocabulary. In this study, respondents, had a level of understanding of 99 percent for a good understanding of meaning classification into Indonesian vocabulary and 98.7 percent for a good understanding of meaning classifications into the correct Malaysian vocabulary.